SUSTAINABLE GREEN CITY LOGISTIC SOLUTION FOR THE PRAGUE AGGLOMERATION AND RETAIL CHAIN (Perner's Contacts, 2020)
During the 20th century, population growth and changes in the business environment also led  to a change in mobility requirements. Gradually, there was an increase in transport performance in the area of passenger and freight transport. These trends are also characteristic of the 21st century, when it is also possible to talk about the fundamental development of modern information and communication technologies. The sustainable and green city logistics deals with all transport (passenger and freight) and includes material and goods flows and movements of people inside and outside the city and agglomeration with respect to the sustainability pillars. This article deals with the possibilities of supplying Lidl Česká republika v.o.s. (hereinafter Lidl) stores in Prague agglomeration from the planned logistic centre in Buštěhrad. Two scenarios are tested in terms of total carbon dioxide emissions produced: standard way of distributing goods to stores (scenario A) and sustainable and green way of distributing goods to stores (scenario B). The scientific methods and approaches are used in this article, there are: scenario analysis, vehicle routing problem with pickup and delivery with time windows and carbon dioxide emissions calculation approaches.